2012
DOI: 10.1002/jctb.2761
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline sulfite/anthraquinone pretreatment followed by disk refining ofPinus radiataandPinus caribaeawood chips for biochemical ethanol production

Abstract: BACKGROUND: Alkaline sulfite/anthraquinone (ASA) cooking of Pinus radiata and Pinus caribaea wood chips followed by disk refining was used as a pretreatment for the production of low lignified and high fibrillated pulps. The pulps produced with different delignification degrees and refined at different energy inputs (250, 750 and 1600 Wh) were saccharified with cellulases and fermented to ethanol with Saccharomyces cerevisiae using separated hydrolysis and fermentation (SHF) or semi-simultaneous saccharificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Alkaline-sulfite chemithermomechanical pretreatment has proved to be an efficient way to reduce the recalcitrance of wood and grass lignocellulosic materials. 6,8,10,21 In grasses such as sugar cane bagasse, a previous study has demonstrated that efficient hydrolysis of polysaccharides in the pretreated material can be obtained even with modest delignification and a high yield of pretreated solids (65-85%). 6 In the present work, sugarcane bagasse was pretreated with the alkaline-sulfite process under mild conditions with varied cooking times ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline-sulfite chemithermomechanical pretreatment has proved to be an efficient way to reduce the recalcitrance of wood and grass lignocellulosic materials. 6,8,10,21 In grasses such as sugar cane bagasse, a previous study has demonstrated that efficient hydrolysis of polysaccharides in the pretreated material can be obtained even with modest delignification and a high yield of pretreated solids (65-85%). 6 In the present work, sugarcane bagasse was pretreated with the alkaline-sulfite process under mild conditions with varied cooking times ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Direct comparison with reported data in literature is not straightforward since the process variables (selected raw material, pretreatment and the conditions of solid and enzyme loadings used in the saccharification and fermentation) may vary substantially. Nevertheless, literature reported works comparing strategies of saccharification and fermentation [43][44][45]. Ethanol concentration (39.9 g/L) from acid treated rapeseed (180°C for 20 min and 0.5% H 2 SO 4 ) by SHF was higher than results obtained by SSF and presaccharification and simultaneous saccharification and fermentation (PSSF) at high solid loadings, 20% of solids [43].…”
Section: Effect Of Autohydrolysis Severity On Ethanol Productionmentioning
confidence: 98%
“…The three microorganisms proved to be suitable for fermenting sugars to ethanol in SSSF strategy. In a recent work, Franco et al [38] carried out the SSSF process (24 h of presaccharification and 24 h of SSF) using delignified Pinus radiata and S. cerevisiae, resulting in the production of 15.5 g/L of ethanol with a yield of 90.0%. Furthermore, Gonçalves et al [15] reported ethanol production and ethanol yield values by S. cerevisiae, P. stipitis and Z. mobilis in SSSF using CFM pretreated by autohydrolysis of 7.71, 8.78 and 7.63 g/L, 90.09%, 87.25% and 89.16%, respectively.…”
Section: Sourcementioning
confidence: 99%